Revision of Batrachospermum section Virescentia (Batrachospermales, Rhodophyta) with the establishment of the new genus, Virescentia stat. nov. - Necchi Jr, Orlando [UNESP]; Agostinho, Douglas C. [UNESP]; Vis, Morgan L. (Adac-cryptogamie, 2018)
In recent years, sections of the paraphyletic genus Batrachospermum have been investigated using DNA sequence data, as well as morphology and some have been raised to genera in order to resolve this paraphylly. The species of Batrachospermum section Hrescentia form a well-supported Glade and we propose the raising of this section to the genus Hrescentia stat. nov. In addition, we re-evaluated the characters used to circumscribe species by reexamination of type specimens and new collections in historically important areas. Of the eleven previously accepted species, we recognize five species and a new species is proposed as follows: V. crispata, V. gulbenkicma (synomyms V. azeredoi and V. fetreri), V. hehninthosa (type species), V. viride-americana sp. nov., V. viride-brasiliensis and V vogesiaca. The species are circumscribed on the basis of morphological characteristics (shape of fascicles, occurrence of secondary fascicles, disposition of carpogonial branches and size of carpogonia), geographic distribution, and DNA sequence data (rbcL and COI-5P). Descriptions, identification key and photomicrographs are presented for each recognized species. Two potential species from Japan based on DNA sequence data remained undescribed due to lack of voucher specimens for morphological observation. Other species previously assigned to the section rirescentia arc referred to other genera of Batrachospermales based on morphology (disposition of carpogonial branches, shape of trichogynes, types of gonimoblast filaments and arrangement of carposporophytes).
Keywords: COI-5P; Batrachospermales; biogeography; morphology; phylogeny; rbeL; revision; Rhodophyta; taxonomy